Defining accuracy in the use of Kinect v2 for exercise monitoring - Woolford, K. (Proceedings of the 2nd International Workshop on Movement and Computing, 2015)
This paper focuses presents a comparison of accuracy and precision between Kinect v2 (low-cost, markerless) and Qualisys motion capture (expensive, marker-based system) for use in healthcare applications. The paper discusses differences between marker-based and markerless tracking through an examination of accuracy (closeness of a measured quantity to its actual value) and precision (or the proximity of repeated measurements) and the difference between precisely tracking markers, but inferring the body structure between them vs directly, but imprecisely tracking body parts. The paper discusses issues detracting from the accuracy of marker-based tracking including human-error in marker-placement and varying methods of post-processing marker data to infer joint or bone centers. The paper then presents a comparison of the Kinect for Windows V2 (K4Wv2) against a clinical system, and suggests situations where the Kinect system may be useable in a healthcare environment.